3D channel modeling and space-time correlation analysis for V2V communications - Wenbo ZENG; Yigang HE; Bing LI; Guolong SHI; Feng ZHAO (Tongxin xuebao)
To match complex wireless propagation scenarios,an improved 3D geometry-based stochastic model was proposed for vehicle to vehicle (V2V) communications channel.The exact relationship between the azimuth angle and elevation angle was taken into account and the corresponding space–time correlation function and space–Doppler power spectral density were derived,and the influence of important factors was analyzed.The observations and conclusions show that correlation characteristics is closely related to distribution of the scatterers and the angle of the antenna array under the non-isotropic scattering environment and is affected by the elevation angle of the antenna array under the isotropic scattering environment.And the space-time correlation characteristics in high vehicular traffic density is significantly lower than that in low vehicular traffic density.The corresponding simulation model is also derived by using a reasonable parameter calculation method.The simulation results validate the rationality of proposed model.It greatly improves analysis and simulation efficiency of V2V MIMO system.